Recent Constitutional Developments in Nepal - DEVARAPALLI, GOWTHAM (IJRDO - Journal of Social Science and Humanities Research, 2017)
Regional disparities do exist in every part of the world. The question remains how effective we addressed it. The recent promulgation of Nepali Constitution had opened the Pandora box. Though Nepal is the oldest Nation state in South Asia, the Political Institutions are very much new to it. The Monarchy which ruled Nepal for 250 years had kept all the institutions in its iron grip. With both its neighbors, India and China intervening in its domestic affairs regularly, Nepal is left out with very little room for an independent policy. It takes time for the growth of institutions and achieving some strength. This paper examines the recent constitutional developments in Nepal and studies how it had addressed the questions of existing social, political and economic inequalities.